Outcomes of Laparoscopic Ventral Hernia Repair in Obese patients - Muhammad Najam Iqbal, Ashfaq Nasir Khan, Muhammad Shahid Khan, Urwa Ashfaq Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Obesity is a risk factor for primary ventral hernia. Surgery is deferred in obese patients because of overweight but most of patients present in emergency with obstructed /strangulated hernia in which outcome is poor. Aim: To compare the primary outcomes (seroma ,surgical site infection and recurrence) and secondary outcomes (duration of surgery and postoperative pain) in obese and non obese patients after laparoscopic primary ventral hernia repair. Study design: Prospective comparative study Setting & duration: B V Hospital /Quaid-e-Azam Medical College Bahawalpur, 01-01-2019 to 31-08-2021 Method: This study was done on 70 patients above the age of 25 years undergoing laparoscopic IPOM (intraperitoneal onlay mesh ) after closure of fascial defect for primary ventral hernia. Patients with history of obstructed /strangulated hernia were excluded. Patients were divided into 2 groups( Patients with BMI <30 kg/m2 - Group A and patients with BMI ≥ 30 kg/m2- Group B). Data was calculated regarding patient’s age ,sex, BMI, comorbidities, type of hernia, hernia size, primary outcome (postoperative complications-seroma ,surgical site infection and recurrence) and secondary outcome (duration of surgery and pain). Statistical analysis using SPSS version 22 was done and it was considered significant when p value was <0.05. Results: 29 (41.43%) had BMI < 30 kg/m2 and 41 (58.57%) had BMI ≥ 30 kg/m2 .The most common comorbidity was diabetes mellitus (17.1%) in both groups. 38 patients presented wiyh paraumblical hernia and 32 patients with epigastric hernia. A significant correlation between size of defect and post operative complications. (p value 0.042) was found. A significant correlation between comorbidities and complications was also found (p value 0.001). Complications being more common in group B patients but were not statistically significant (p value 0.979). Duration of surgery being higher in group B patients but was not statistically significant.(p value 0.194). There was no significant difference in postoperative pain in both groups. Conclusion: Obesity has no significant effect on postoperative complications ( seroma, surgical site infection and recurrence), duration of surgery and postoperative pain after laparoscopic IPOM repair. Comorbidities are significantly associated with postoperative complications rather than increased BMI. So surgery should not be delayed in obese patients.